The Effect of Roundtable Technique to the Students’ Reading Comprehension Achievement In Narrative Text To The Second Year Students MA HM Tribakti Kediri - Riwayatiningsih, Rika -; Muazizah, Heni Lailatul (Universitas Nusantara PGRI Kediri, 2016)
Reading is one of the language skills which is very important to develop students’ knowledge in their studies. To make students understand what they read, it needs techniques. This study aims at finding the effect of roundtable technique to their reading ability. roundtable technique is a technique in which the students are in teams, write a response on their own piece of paper, pass their papers clockwise so each teammate can add to the prior responses. It is an experimental study using One-group Pretest-Posttest design. The data were taken from one class consisting 26 students of the elevent grade of MA HM TribaktiLirboyo Kediri. The data were collected using pre-test, treatment and then post-test. Then the data were analyzed using T-test formula. From data analysis, it can be found that the mean score of post-test (89,92) is higher than mean score of pre-test (58,07). The T-score (at the degree of freedom of 26 is 156,73, that is higher than the t-table at the level of significance of 1% 2,787 and 2,060 at the level of significance of 5%. So, the T-score (156,73) ≥ T-table, and the level of significance is 1 % (2,787). It means that it is very significant, so the H0 is rejected and Ha is accepted. It can be concluded that Roundtable Technique is effective to increases students’ reading comprehension. So it is recommended that Roundtable Technique can be used in teaching reading . The other writers are expected to conduct a better research about Roundtable Technique because small Roundtable Technique is effective to use.